PENGARUH VARIASI EMITTER PADA JARINGAN IRIGASI TETES PIPA PVC BERTINGKAT TERHADAP DISTRIBUSI DAN KESERAGAMANAN IRIGASI - I DEWA GEDE JAYA NEGARA; ANID SUPRIYADI; EKO PRADJOKO; ATAS PRACOYO; YUSRON SAADI; I WAYAN YASA (GANEC SWARA, 2024)
Test efforts to find alternatives to increase the even distribution of irrigation water on service land. The results of previous research conducted by researchers show that drip irrigation which is designed in stages with a water source from a drip irrigation tank using two types of emitters in a multi-stage drip irrigation system provides different irrigation water distribution results, so it is necessary to find a solution. so that irrigation can occur evenly. To get an alternative that might be tested is to use several types of emitters in the PVC pipe drip point holes, because these tools already exist on the market. This research aims to determine the effect of using two types of emitters, namely 2 lt/min and 4 lt/min emitters on distribution of irrigation water in a 4-tiered drip irrigation network. The test data analyzed includes irrigation distribution data, flow discharge data and irrigation uniformity (Cu), and the results of the analysis are presented in the form of tables and graphs and discussed before conclusions are drawn. The analysis results show that the average Cu for the two types of emitters is above 97%, which is very good and the two emitters have a very even distribution. The difference in distribution volume for each emitter, for a 2ml/min emitter is around 1ml -2 ml and for a 4 ml/min emitter it is 1ml -2 ml, with an irrigation network flow rate of around 84ml/min – 99.7 ml/min.